Long-Term Follow-Up of Accelerated Transepithelial Corneal Crosslinking for Post-LASIK Ectasia: A Pilot Prospective Observational Study - Tian, Mi; Zhang, Xiaoyu; Jian, Weijun; Sun, Ling; Shen, Yang; Zhou, Xingtao (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Keratectasia after corneal refractive surgery is a rare but serious postoperative complication, and reports on accelerated transepithelial corneal crosslinking (ATE-CXL)-based treatment of patients with post-laser-assisted in situ keratomileusis (LASIK) ectasia are limited. Therefore, this study evaluated the long-term efficacy and safety of ATE-CXL for progressive post-LASIK ectasia. Methods: This prospective observational study was conducted at the Eye and ENT Hospital, Fudan University, Shanghai, China, and 25 eyes from 25 patients with post-LASIK ectasia undergoing ATE-CXL were examined. Clinical examinations were conducted preoperatively and postoperatively to assess parameters such as manifest refraction, corrected distance visual acuity (CDVA), endothelial cell density; keratometry, corneal thickness, posterior elevation and topometric indices were measured using Pentacam; sectoral pachymetry and epithelial thickness were evaluated using optical coherence tomography. A paired t-test, Wilcoxon rank-sum test, Kruskal-Wallis test, and repeated measures analysis of variance were used for statistical analysis. Results: Participants were examined for an average of 46 months. No severe complications occurred during or after ATE-CXL. CDVA improved from 0.25 ± 0.31 preoperatively to 0.15 ± 0.17 postoperatively (p = 0.011). Maximum keratometry decreased from 55.20 ± 8.33 D to 54.40 ± 7.98 D, with no statistical significance (p = 0.074), and the central corneal thickness increased from 414.92 ± 40.96 μm to 420.28 ± 44.78 μm (p = 0.047) at the final follow-up. Posterior elevation, pachymetry, and epithelial thickness remained stable (p > 0.05) throughout the follow-up. No significant differences were noted in topometric indices, except the central keratoconus index, which decreased significantly (p < 0.001) at the final follow-up. Conclusion: Improvements in CDVA and stabilization in corneal keratometry and posterior elevation after ATE-CXL were noted at the 46-months follow-up, demonstrating that ATE-CXL is a safe and effective treatment for progressive post-LASIK ectasia.